CULTURE-BOUND TERMS IN TRANSLATION: STRATEGIES AND ETHICAL CONSIDERATIONS (International Conference on Medical Science, Medicine and Public Health, 2025)
Culture-bound terms, also called nationally and culturally specific units or realia, are words and expressions rooted in the traditions, institutions, and everyday practices of a community. Their translation poses not only linguistic but also ethical challenges. This paper outlines key strategies for handling culture-bound terms and considers the ethical implications of translation choices.